Avaliação de melhorias na utilização de ferramentas do PCP em uma empresa de porte médio do ramo metalúrgico - Alves, Rafael Guastalle (2019)
With changes in the global marketplace, the need for companies to adapt to new technologies and processes to remain competitive has created. The objective of this paper is to evaluate the improvements in Production Planning and Control (PPC) tools in a medium metal range company during the implementation of an integrated information system. For this, it was made a survey of quantitative data, formulation of indicators, elaboration of evaluation criteria and the execution of the study in two phases with monitoring of the activities of Planning and Production Control. About 3003 items were modified in this work, mainly between finished products and components as well as their manufacturing routes and / or data sheets making them suitable as control and information tools. From the changes, it was evaluated that the improvements were significant and satisfactory but there is still need for improvements in the activities of pointing and implementation of new indicators.